Using Parkour for Teaching Personal and Social Responsibility: Implications for Practitioners: Editor: Ferman Konukman. Issue 8 (12th October 2016) - Cabrera Gadea, Lucia; Jacobs, Jenn M.
Abstract : The purpose of this article is to explore the advantages of engaging youth in the sport of parkour and to provide physical education teachers and after-school club coaches with strategies to integrate personal and social responsibility lessons while practicing parkour.